The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/insects13010002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Selective Signature Analysis Revealed Insecticide Resistance Mechanisms in Cydia pomonella

Abstract: The codling moth, Cydia pomonella L. (Lepidoptera, Tortricidae), is a serious invasive pest of pome fruits. Currently, C. pomonella management mainly relies on the application of insecticides, which have driven the development of resistance in the insect. Understanding the genetic mechanisms of insecticide resistance is of great significance for developing new pest resistance management techniques and formulating effective resistance management strategies. Using existing genome resequencing data, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…C. pomonella is a destructive pest of pome fruits worldwide, and the use of chemical insecticides has been considered the most effective and direct control measure against this pest. ,, It has been demonstrated that the overuse of insecticides inevitably leads to the challenging problems of insecticide resistance, which causes almost all pests to be uncontrollable again, including C. pomonella. ,, Pests have developed multiple complex regulatory mechanisms to enhance their activity of detoxification enzymes to address persecution caused by insecticide exposure. , In this study, we characterized the transcription factor CpAhR and confirmed that it can effectively activate the expression of key resistance detoxifying genes belonging to GST and P450 superfamilies as well as the enzyme activity of GST but not the P450, thereby increasing the resistance to lambda -cyhalothrin in C.…”
Section: Discussionmentioning
confidence: 99%
“…C. pomonella is a destructive pest of pome fruits worldwide, and the use of chemical insecticides has been considered the most effective and direct control measure against this pest. ,, It has been demonstrated that the overuse of insecticides inevitably leads to the challenging problems of insecticide resistance, which causes almost all pests to be uncontrollable again, including C. pomonella. ,, Pests have developed multiple complex regulatory mechanisms to enhance their activity of detoxification enzymes to address persecution caused by insecticide exposure. , In this study, we characterized the transcription factor CpAhR and confirmed that it can effectively activate the expression of key resistance detoxifying genes belonging to GST and P450 superfamilies as well as the enzyme activity of GST but not the P450, thereby increasing the resistance to lambda -cyhalothrin in C.…”
Section: Discussionmentioning
confidence: 99%
“…C. pomonella is a destructive pest of pome fruits worldwide that causes a great loss of both quality and yield, and the use of chemical insecticides has been considered the most effective and direct control measure [3,34,35]. It has been demonstrated that prolonged exposure to insecticides inevitably leads to the problem of an increase in insecticide resistance, which causes almost all pests will be uncontrollable again, including C. pomonella [7,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Injection of dsRNA targeting two such transcripts, coding for CYP4c1 and CYP9e2 , were investigated in this study. Besides CYP4c1 and CYP9e2 overexpression observed in L. decemlineata exposed to clothianidin, previous work revealed a potential relevance for these targets with respect to insecticide resistance in insects exposed to various compounds, further supporting their potential importance in insecticide management [ 37 , 38 ]. Adult L. decemlineata injected with dsRNA targeting the latter notably revealed significant differences in insects treated with clothianidin when compared with insects used as controls, suggesting an underlying function for this transcript with respect to clothianidin response in this insect.…”
Section: Discussionmentioning
confidence: 91%